Use of morphometry in the arborization of Paragominas city, Pará, Brazil, with Handroanthus impetiginosus (Mart. ex DC.) Mattos (Bignoniaceae) - Victor Pereira de Oliveira; Michael Douglas Roque Lima; Walmer Bruno Rocha Martins (Agro@mbiente On-line)
The study of the morphometry of individual trees, especially those planted in urban spaces has become important for the effective planning of available space use. The objective of this study was to describe the morphometric variables for individuals of the species Handroanthus impetiginosus Mattos (pink trumpet tree, pink ipe) used for urban tree-planting in the municipality of Paragominas, Pará State, northern Brazil. The study evaluated 15 continuously distributed individual trees per street, one street per neighborhood. For each sampled tree, the dendrometric data were collected, which were later converted to morphometric variables. Mean values for Total Height (TH), Canopy Width (CW), Diameter at Breast Height (DBH) and Canopy Diameter (CD) were 6.48, 3.98, 0.19 and 4.95, respectively. Canopy Ratio (CR), Slenderness Factor (SF) and Salience Index (SI) values of 61.95, 35.16 and 26.44 were calculated. Mean Coverage Index (CI) was 0.78, and Canopy Form (CF) was considered to be more elongated, both vertically and horizontally and, with a mean value of 1.35, could be used as a criterion to determine the need for silvicultural intervention. Coefficient of Variation (CV) values lay between 20 and 43%, showing high variation due to the lack of experimental control and the action a wide-variety of growth-influencing variables. There was a moderate positive correlation for the SG and SI (0.522) and for CI and HR (0.631). The morphometric variables obtained from H. impetiginosus individuals reveal growth form data that should be considered when planning new urban areas for implantation.